Role of spatial tools in public health policymaking of Bangladesh: opportunities and challenges - Kim, Dohyeong; Sarker, Malabika; Vyas, Priyanka (© 2016 Journal of Health, Population and Nutrition, 2017)
This article was published in the Journal of Health, Population and Nutrition [© 2016 by Kim et al. ] and the definite version is available at : https://doi.org/10.1186/s41043-016-0045-1. The Journal's website is at: https://jhpn.biomedcentral.com/articles/10.1186/s41043-016-0045-1